Validation of the Alif Module: A Transtheoretical Model Intervention for Promoting Positive Behavior Among Indonesian Adolescents With Self-Harm Tendencies - Alini, Alini; Said, Faridah Mohd; Aprilla, Nia; Nofrika, Bri (Oshada, 2026)
Self-harm among Indonesian adolescents is an increasingly alarming issue, with its rising prevalence posing significant threats to both mental and social health, thereby highlighting the urgent need for effective, locally developed, and culturally relevant interventions. However, interventions specifically designed within the context of psychiatric nursing in Indonesia remain limited, resulting in suboptimal support for high-risk adolescents. In response to this need, this study aimed to develop and validate the ALIF Module as a psychosocial nursing intervention based on the Transtheoretical Model (TTM), designed to promote positive behavioral change and prevent self-harm through a stage-based approach aligned with adolescents’ readiness to change. The study employed a mixed-methods validation process involving three psychiatric nursing experts and one linguist, who conducted expert reviews across six content indicators and eight language indicators, with quantitative data analyzed using the Content Validity Index (CVI) to assess validity in both domains. The findings indicated that the ALIF Module achieved a content CVI of 89.13%, demonstrating high feasibility and strong content validity, while linguistic validation yielded a mean CVI of 92.75%, confirming that the module is communicative and adheres to standard Indonesian language conventions; all experts agreed that the module met behavioral intervention criteria, was easily understood by adolescents, and effectively fostered positive attitudes and knowledge regarding self-harm prevention. Overall, the ALIF Module is a valid and promising psychiatric nursing intervention suitable for implementation in school and community-based mental health programs to reduce self-harm risk among adolescents, with further research recommended to evaluate its long-term effectiveness and adapt it to diverse cultural contexts within Indonesia and beyond.